Oromandibular dystonia: a serious side effect of capecitabine - van Pelt-Sprangers, Melanie JM (BMC Cancer, 2015)
BACKGROUND: Capecitabine has activity against several types of cancer. In 10-15% of patients treated with capecitabine, treatment is discontinued because of serious adverse reactions, mostly within the first weeks of treatment. CASE PRESENTATION: A 56 year-old female patient presented at the emergency department after ten days of chemotherapy with progressive airway obstruction and complaints of numbness of the tongue. She also had difficulty swallowing and was unable to speak. Laboratory findings were completely normal and no co-medication was used, in particular no dopamine antagonists. A diagnosis of oromandibular dystonia due to capecitabine use was made. After the anticholinergic drug biperiden (Akineton) was given intravenously, complaints disappeared within twenty minutes. Due to an early discontinuation of biperiden, however, the symptoms of oromandibular dystonia recurred. Again, she was successfully treated with an anticholinergic drug. Capecitabine was permanently discontinued. Three days after the initial presentation the anticholinergic drug was stopped after which symptoms did not reappear. CONCLUSION: The case highlights the need for awareness that capecitabine may potentially lead to severe life-threatening complaints of oromandibular dystonia. We hypothesize that capecitabine passed the blood brain barrier which led to a disruption within the basal ganglia in this case. Prompt treatment with an anticholinergic drug and cessation of capecitabine in the patient case led to disappearance of complaints.